Organic, Gas, and Element Geochemistry of Hydrothermal Fluids of the Newly Discovered Extensive Hydrothermal Area in the Wallis and Futuna Region (SW Pacific) - C. Konn; J. P. Donval; V. Guyader; E. Roussel; E. Fourré; P. Jean-Baptiste; E. Pelleter; J. L. Charlou; Y. Fouquet (Geofluids)
Two newly discovered hydrothermal vent fields of the Wallis and Futuna region, Kulo Lasi and Fatu Kapa, were sampled for fluid geochemistry. A great geochemical diversity was observed and assigned to the diversity of lithologies as well as the occurrence of various processes. Kulo Lasi fluids likely formed by interaction with fresh volcanic rocks, phase separation, and mixing with magmatic fluid. Conversely, the geochemistry of the Fatu Kapa fluids would be mostly due to water/felsic lavas reactions. In terms of organic geochemistry, fluids from both fields were found to be enriched in formate, acetate, and semivolatile organic compounds (SVOCs): n-alkanes, n-fatty acids, and polyaromatic hydrocarbons (PAHs). Concentrations of SVOCs reached a few ppb at most. The distribution patterns of SVOCs indicated that several processes and sources, at once of biogenic, thermogenic, and abiogenic types, likely controlled organic geochemistry. Although the contribution of each process remains unknown, the mere presence of organics at the μM level has strong implications for metal dispersion (cycles), deposition (ore-forming), and bioavailability (ecosystems), especially as our fluxes estimations suggest that back-arc hosted vent fields could contribute as much as MOR to the global ocean heat and mass budget.